Design of enhanced gain patch antenna at 2.4 GHz and 3.5 GHz for wireless application - Azeman, Mohammad Addad; Abdul Malek, Norun; Mohamad, Sarah Yasmin; Mohd Ghazali, Mohd Ifwat (2022)
In this work, the analysis of patch antenna design at the resonant frequency of 2.4 GHz and 3.5 GHz are presented. Both proposed antennas made of RT Duroid 5880 are designed and simulated using CST Studio Suite software. The antennas are designed, and their performances are examined. The antennas have been designed based on the size improvement technique to improve the fabrication tolerance. The characteristics of both antennas’ including return loss, radiation pattern, surface current and directivity or gain were compared. The optimization of patch measurement to achieve the desired resonant frequency were also displayed.